3 Cycles New Medical Consultation Model - AlAlkaabba, Abdulaziz Fahad (New Advances in Medicine and Medical Science Vol. 1, 2023)
The purpose of this study is to introduce and evaluate the Al-Kaabba 3 Cycle Consultation Model, a new clinical consultation model. Conducting a medical consultation in practice is one of the elements of good medical care. A cross-sectional questionnaire-based investigation was carried out with 97 medical students from Imam Mohammad Ibn Saud Islamic University (IMISU) who were trained using this model. There were 66 males and 31 females among the students. This new technique was also evaluated by some expert Medical education specialists. SPSS was used to analyze the collected data. The great majority of enrolled students (94; 96.9%) agree strongly that AlKaabba 3-cycles assisted them in gathering relevant patient information and feeling comfortable using it during their training. Almost all of them (96; 99%) agree that the 3-cycles new consultation Method helped them confidently take the patient's medical history and evaluation, and they recommend that it be taught and practiced on a regular basis. The starting consultation as introducing yourself and greaten and welcome the patients is very important also closing consultation and thanking your patient were priority in this new consultation module Creating and practicing New consultation methods teaching tools produce positive results and assist medical students and health care providers in learning and practicing in their roles.